Synthesis of flavonoid compounds [electronic resource] - 263231 Adiana Mohamed Adib; Farediah Ahmad; Muhammad Sum Idris (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains(Kimia) - Universiti Teknologi Malaysia, 2007